THE EFFECT OF CONTEXTUAL GUESSING TECHNIQUE ON STUDENTS’ READING COMPREHENSION ACHIEVEMENT IN DESCRIPTIVE TEXT - RatnaPurnama Sari; Willem Saragih (Universitas Negeri Medan, 2016)
This study deals with the effect of Contextual Guessing Technique (CGT) on students’ reading comprehension achievement in descriptive text. The problem of the study is to find out whether Contextual guessing Technique significantly affects students’ achievement in reading descriptive text or not. This study was conducted by using experimental design. The population of the study was the students of eighth grade of SMP Negeri 3 Perbaungan in academic years 2014/2015, there were 5 parallel classes of grade VIII. There were two classes selected to be sample. The experimental group (VIII-2) was taught by using CGT, while the control group was taught by applying conventional technique. The data of the study was obtained from the students’ scores of reading test. There were two kinds of test used in this study. They were pre-test and post-test. The data were analyzed by applying t-test formula. After analyzing the data, the result of the study showed that t-observed (2,322) was higher than t-table (2,024) (t-observed > t-table) at the level of significance of p=0,05 and the degree of freedom (df) = 38. Thus, it can be concluded that applying CGT significantly affects students’ achievement in reading descriptive text, or in other words, the null hypothesis is rejected; therefore, the alternative hypothesis is accepted.